Abundance and Diversity of Methanotrophs and Propanotrophs in Soils above Yangxin Oil Reservoir, China. Issue 8 (13th September 2016) - Liu, Ya-Ci; He, Ze; Zhang, Sheng; Yin, Mi-Ying; Ning, Zhuo; Zhang, Cui-Yun
ABSTRACT: Methanotrophs have long been used as an important biological indicator for prospecting of oil and gas, while the indication of propanotrophs in hydrocarbon micro-seep systems is still poorly investigated. In this study, the abundance and diversity of the methanotrophic pmoA gene and the propanotrophic prmA gene as target genes were investigated in soils above Yangxin oil reservoir and Beiguan non-petroliferous area using molecular biological techniques. A total of 14 soil samples were collected at different depths (5, 20, 50, 100, 150, 200 and 250 cm) of two 2.5-m soil profiles located separately within the oil field and the non-petroliferous area for analysis of fluorescent quantitative real-time polymerase chain reaction (RT-PCR) (14 samples) and clone libraries (4 samples). The results demonstrated high presence of the propanotrophic prmA gene ranging from 7.68 × 10 5 to 2.29 × 10 7 copies/g dw (gene copies per gram soil of dry weight) in soil from the oil field relative to the non-petroliferous area for which the same measurements yielded results all below detection limit except for the 5-cm sample. On the other hand, oil field soil yielded much lower content of the methanotrophic pmoA gene (below detection limit to 5.6 × 10 2 copies/g dw) than the non-petroliferous area (1.14 × 10 3 copies/g dw to 1.26 × 10 5 copies/g dw) below 20-cm depth due to influence of biogenic methane, implying that propanotrophs may be better indicator bacteria for prospecting of oil and gas. Almost all pmoA clones of two 50-cm soil samples phylogenetically belonged to Gamma -Proteobacteria and the predominant pmoA OTUs were all uncultured bacteria. All prmA clones of two 5-cm soil samples were derived predominantly from Actinobacteridae (25.7%) and Alpha -Proteobacteria (74.3%), and all dominant prmA OTUs were also clustered with uncultured bacteria. Our results confirm that propanotrophs may be better indicator bacteria for prospecting of oil and gas and enrich the knowledge on diversity of methanotrophs and propanotrophs in the oil field and the non-petroliferous area.